Association Between Anticoagulation Outcomes and Venous Thromboembolism History in Chronic Thromboembolic Pulmonary Hypertension - Zhu, Yong-Jian; Zhou, Yu-Ping; Wei, Yun-Peng; Xu, Xi-Qi; Yan, Xin-Xin; Liu, Chao; Zhu, Xi-Jie; Liu, Zi-Yi; Sun, Kai; Hua, Lu; Jiang, Xin; Jing, Zhi-Cheng (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between anticoagulation outcomes and prior history of venous thromboembolism (VTE) in chronic thromboembolic pulmonary hypertension (CTEPH) has not been established. This study aimed to compare the efficacy and safety of anticoagulation treatment in CTEPH patients with and without prior history of VTE. Methods: A total of 333 CTEPH patients prescribed anticoagulants were retrospectively included from May 2013 to April 2019. The clinical characteristics were collected at their first admission. Incidental recurrent VTE and clinically relevant bleeding were recorded during follow-up. The Cox proportional regression models were used to identify potential factors associated with recurrent VTE and clinically relevant bleeding. Results: Seventy patients (21%) without a prior history of VTE did not experience recurrent VTE during anticoagulation. Compared to CTEPH patients without a prior history of VTE, those with a prior history of VTE had an increased risk of recurrent VTE (2.27/100 person-year vs. 0/100 person-year; hazard ratio [HR]: 8.92; 95% confidence interval [CI]: 1.18-1142.00; P = 0.029) but a similar risk of clinically relevant bleeding (3.90/100 person-year vs. 4.59/100 person-year; HR: 0.83; 95% CI: 0.38-1.78; P = 0.623). Multivariate Cox analyses suggested that a prior history of VTE and interruption of anticoagulation treatments were significantly associated with an increased risk of recurrent VTE, while anemia and glucocorticoid use were significantly associated with a higher risk of clinically relevant bleeding. Conclusions: This study is the first to reveal that a prior history of VTE significantly increases the risk of recurrent VTE in CTEPH patients during anticoagulation treatment. This finding should be further evaluated in prospective studies.